Cerebral Venous Sinus Thrombosis Case Series - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Presenting features, co-morbid conditions, treatment, and outcome of cerebral venous sinus thrombosis (CVST) in a consecutive series of children are reported from Department of Paediatric Neurology, Bristol Royal Hospital for Children, UK.